2003
DOI: 10.1016/s0301-4797(02)00204-9
|View full text |Cite
|
Sign up to set email alerts
|

Learning through public involvement in environmental assessment hearings

Abstract: This research examined the opportunities for critical education available to participants of a federal environmental assessment (EA) that includes hearings. The Sable Gas Panel Review, an assessment of a natural gas project situated in the Maritimes, was undertaken between 1996 and 1997. This study documented what participants learned through their experiences and how that learning was facilitated. Primary data collection emphasized the use of semi-structured interviews to record the experientially based obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 16 publications
2
44
0
3
Order By: Relevance
“…According to Fitzpatrick and Sinclair [36], public participation "accentuates the effectiveness of the environmental assessment, actualizes the principles of democracy, ensures that the project meets the needs of the public, assigns legitimacy to a project, provides awareness for conflict resolution for stakeholders, provides a forum for the submission and inclusion of local knowledge in the EA decision, and provides for a more comprehensive consideration of factors on which decisions are made". Analysis of the Barrancones, HydroAysén, Pangue/Ralco and Castilla projects shows that there has been a lack of transparency in the dialogue between the different stakeholders involved: citizens, developers, owners of the projects, and government.…”
Section: The Lack Of Open and Transparent Debate Prior To Project Submentioning
confidence: 99%
“…According to Fitzpatrick and Sinclair [36], public participation "accentuates the effectiveness of the environmental assessment, actualizes the principles of democracy, ensures that the project meets the needs of the public, assigns legitimacy to a project, provides awareness for conflict resolution for stakeholders, provides a forum for the submission and inclusion of local knowledge in the EA decision, and provides for a more comprehensive consideration of factors on which decisions are made". Analysis of the Barrancones, HydroAysén, Pangue/Ralco and Castilla projects shows that there has been a lack of transparency in the dialogue between the different stakeholders involved: citizens, developers, owners of the projects, and government.…”
Section: The Lack Of Open and Transparent Debate Prior To Project Submentioning
confidence: 99%
“…Despite its breadth, the literature on EA participation has largely overlooked women's groups, let alone those of Indigenous women. The literature has charted best practices in Indigenous participation and critiqued past EA processes for not including many of these elements (Fitzpatrick and Sinclair, 2003). Despite the failures of many EA processes to engage in appropriate consultation with Indigenous communities, researchers and practitioners continue to point to them as a way for Indigenous communities to influence resource development (Stevenson, 1997;Gibson, 2006;Galbraith et al, 2007;Fidler, 2008;Gibson, 2008).…”
Section: Indigenous Participation In Easmentioning
confidence: 99%
“…The past two decades have witnessed many process-oriented studies charting best practices for Indigenous participation in EAs (Bishop and Davis, 2002;Fitzpatrick and Sinclair, 2003). In response, several authors have suggested that researchers pay greater attention to how the definition and implementation of participation in EAs is related to control over environmental decision making (Chess and Purcell, 1999;Cashmore et al, 2004;O'Faircheallaigh, 2007O'Faircheallaigh, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Public engagement, including Aboriginal engagement, should strive to be fair, influential, empowering, and lead to social learning (Webler and Tuler, 2000;Poncelet, 2001;Webler et al, 2001;Abelson et al 2003;Fitzpatrick and Sinclair, 2003;Barabas, 2004;Bond et al, 2004;Armitage, 2005;Doelle and Sinclair, 2006;Stewart and Sinclair, 2007). One mechanism for achieving these outcomes is through the provision of participant funding, where resources are made available by governments or the proponent to stakeholders with limited means to ensure their voices are properly heard through the EA process.…”
Section: Public Engagementmentioning
confidence: 99%
“…Approximately 10,000 FN Cree inhabit the Mushkegowuk Territory, living in four coastal FN Sources: Webler and Tuler, 2000;Mulvihill and Baker, 2001;Sosa and Keenan, 2001;Poncelet, 2001;Gibson, 2002;Abelson et al 2003;Fitzpatrick and Sinclair, 2003;Barabas, 2004;Bond et al, 2004;Armitage, 2005;Doelle and Sinclair, 2006;Wood et al 2006;Stewart and Sinclair, 2007 communities along the western James Bay region (Moose Factory, Fort Albany, Kashechewan and Attawapiskat), and one town, Moosenee. Harvesting of wild game and other traditional pursuits are still a way of life for people of the region (Tsuji and Nieboer, 1999).…”
Section: Study Area and Case Backgroundmentioning
confidence: 99%